Advances in PD-1/PD-L1 pathway inhibitors in the treatment of thyroid cancer: mechanisms and clinical therapeutic perspectives - Xizi Li; Xizi Li; Siyuan Gao; Chuchu Shan; Chuchu Shan; Qiling Zhang; Qiling Zhang; Ying Tan; Ying Tan; Ying Tan; Xu Yu; Xu Yu; et al. (Frontiers in Immunology)
Cancer of the thyroid is a endocrine cancer. Although most patients achieve favorable outcomes with surgical resection, radioactive iodine (RAI) ablation, and thyroid-stimulating hormone (TSH) suppression therapy, a subset progresses to advanced or refractory disease. Immune checkpoint inhibitors (ICIs) blocking the PD-1/PD-L1 pathway reactivate T cells, enabling them to identify and eradicate malignant cells, thus reinstating immune surveillance against tumors. This review examines PD-L1 (Programmed Death-Ligand 1) expression in thyroid cancer, exploring its underlying regulatory mechanisms. It also discusses recent advances in PD-1/PD-L1 immune checkpoint inhibition (ICI) therapy. Furthermore, the review highlights regulatory pathways modulating PD-1/PD-L1 expression, including the mTOR pathway, androgen receptor (AR), and the CKS1B/STAT3 pathway. Notably, it summarizes recent clinical developments, such as combination regimens pairing PD-L1 blockade with mutation-targeted therapies, for which the median OS of the targeted combination therapy group was 14.7 months. This therapy has achieved the longest median OS for anaplastic thyroid carcinoma (ATC) patients so far. Additionally, the review examines innovative treatment modalities, offering a thorough synthesis of the existing state and emerging trends in PD-1/PD-L1 immunotherapies.